Antibiotics in periodontal treatment: an umbrella review - Botelho, João; Lyra, Patrícia; Nascimento, Gustavo G.; Leite, Fábio R. M.; Mendes, José João; Machado, Vanessa (Frontiers in Cellular and Infection Microbiology, 2025)
AimAntimicrobial stewardship envisions the appropriate use of antimicrobials, including antibiotics. Antibiotic therapy in Periodontology has been widely investigated over the years. This umbrella review aimed to appraise the methodological quality and meta-analytical strength and validity of the evidence of systematic reviews (SRs) on systemic and local antibiotics in periodontal therapy.Material and methodsAfter registration of the protocol (PROSPERO CRD42024527222), an extensive search, up to March 2024, for SRs that have assessed the effect of antibiotics in periodontal therapy, either nonsurgical and surgical, regardless of the types of patients and type of antibiotic. The methodological quality of SRs was judged using A MeaSurement Tool to Assess systematic Reviews 2. Fail-safe number of Rosenberg explored the number of nonsignificant, unpublished, or missing studies that would be required to change the direction of that evidence.ResultsForty-four SRs, consisting of 221 meta-analyses, were included. The overall methodological quality was low, with only four and two SRs of high or moderate quality, respectively. Out of 221 meta-analyses, 69 indicated that the effect of systemic or local antibiotics was statistically not significant. Twenty-nine meta-analyses from suggestive-to-strong strength from one high and three low methodological quality SRs indicated that the systemic or local antibiotics had a beneficial, statistically significant effect on periodontal health parameters, such as average clinical attachment loss, bleeding on probing or percentage of pocket closure. Of those, four strong evidence meta-analyses from a low-quality systematic review indicated significant and meta-analytically robust but with negligible effect. About 65.5% of the meta-analyses with suggestive to strong evidence are unlikely to change with more future studies.ConclusionThere is no robust evidence to support the use of antibiotics for periodontal management. Systemic antibiotics have a minimal effect on periodontitis and additional studies are unlikely to change the level of evidence.